Asumsi Dasar Keilmuan Filsafat dalam Bimbingan dan Konseling - Nurhafiza, Nurhafiza; Herlinda, Fitra; Ahmad, Raja Rahima Munawarah Raja (Jurnal Bimbingan dan Konseling Terapan, 2023)
This study aims to determine the basic assumptions of scientific philosophy in guidance and counseling. The method of this research is qualitative with a library study approach. that library or library study can be defined as a series of activities related to library data collection methods, reading and recording and processing research materials. The results of the study indicate that philosophy is a science whose material object includes and provides an understanding of the nature of man and various problems in it to achieve the welfare of life, in counseling guidance or philosophy of science requires assumptions, namely the basis of science so that it can produce various sources of other sciences through rationalism, empirical, critical and intuition.  The basic assumptions of philosophy in the study of counseling guidance belong to ontology, which discusses the nature of what exists. As the basis of guidance and counseling, it means that philosophy provides a foundation for guidance and counseling to stand on.